2017
DOI: 10.1017/jfm.2017.239
|View full text |Cite
|
Sign up to set email alerts
|

On the orientational dependence of drag experienced by spheroids

Abstract: The flow around different prolate (needle-like) and oblate (disc-like) spheroids is studied using a multi-relaxation-time lattice Boltzmann method. We compute the mean drag coefficient C D,φ at different incident angles φ for a wide range of Reynolds numbers (Re). We show that the sine-squared drag law2 φ holds up to large Reynolds numbers Re = 2000. Further, we explore the physical origin behind the sine-squared law, and reveal that surprisingly, this does not occur due to linearity of flow fields. Instead, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 17 publications
(15 reference statements)
6
57
0
Order By: Relevance
“…In the present work, we use a D3Q19, MRT lattice Boltzmann method to simulate the fluid flow. The numerical method is adequately explained and validated in our previous works . The evolution of particle distribution function ∣ f 〉 is computed as f(),bold-italicr+eαnormalΔtt+normalΔtfalse〉=f()bold-italicr,tfalse〉M1trueS^()m()bold-italicr,tfalse〉meq()bold-italicr,tfalse〉, for position r with discrete velocities e α in directions α = 1, 2…, 19.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work, we use a D3Q19, MRT lattice Boltzmann method to simulate the fluid flow. The numerical method is adequately explained and validated in our previous works . The evolution of particle distribution function ∣ f 〉 is computed as f(),bold-italicr+eαnormalΔtt+normalΔtfalse〉=f()bold-italicr,tfalse〉M1trueS^()m()bold-italicr,tfalse〉meq()bold-italicr,tfalse〉, for position r with discrete velocities e α in directions α = 1, 2…, 19.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we developed drag, lift, and torque closures for three different nonspherical particles from the viscous Stokes regime upto the high Re regime of Re = 2000, involving complex, unsteady flows . In an earlier work, we reported the interesting finding that the drag coefficient C D at different incident angles ϕ follows a sine‐squared scaling given by CnormalD,ϕ=CnormalD,ϕ=0°+()CnormalD,ϕ=90°CnormalD,ϕ=0°sin2ϕ. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laws (15) and (16) obtained using linearity of Stokes equations might be valid for other aspect ratios. Indeed the linearity of Stokes equations remains valid for all aspect ratios and these laws have proven to be valid even for spheroids of high aspect ratio [53]. The assumption C Dθ=0 • ≈ 1/2C Dθ=90 • is also supposed to give more accurate results as L/D increases [4].…”
Section: Simple Laws For the Hydrodynamic Force And Torquementioning
confidence: 99%
“…Sanjeevi and Padding [53] studied recently the flow past oblate spheroids. They observed that (8) and (9) obtained in the Stokes regime match well numerical results even in inertial −-− (6) and (7).…”
Section: Simple Laws For the Hydrodynamic Force And Torquementioning
confidence: 99%